Gestes, savoirs et normes de métier des enseignants vus par des collégiens - Marie-Sylvie Claude; Patrick Rayou (Nantes Université, 2019)
This article reports on a research that studies fifty middle school students analyzing teachers' gestures. These students were invited, during individual interviews, to observe and analyze the interactions between pupils of a same class of 3rd and two of their teachers in two video sequences. Students refer more or less explicitly to educational values, which they believe should govern classroom situations in order to guarantee students both the respect of their person and the development of their knowledge. They subordinate access to these values to the respect by the teacher of more or less critical or doxic standards. Taking into account, in addition to the standards of the teachers, these standards of the college students, can help to understand the joint action between teachers and pupils, and the didactic contracts which result from it